An overview of the services of the eminent Sufi "Hazrat Sheikh Hamza Makhdoom (may Allah have mercy on him)" in spreading Islam in Kashmir: کشمیرمیں اسلام کی اشاعت میں نامور صوفی "حضرت شیخ حمزہ مخدوم (رحمتہ اللہ علیہ)" کی خدمات کا جائزہ - Gull, Dr. Shabnum; Khawaja, Dr. Anbreen; Maroof, Jamila (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Kashmir is the land of Sufi Saints. The Sufi saints change the society and culture of Kashmir through their teachings and preaching of Islam. So the famous Sufi saint Hazrat Sheikh Hamza Mekhdoom also play a vital role to change the society. This paper is regarding to the Sufi saint Hamza Makhdoom’s life history and their status as religious person, Sufi mystic, scholar and spiritual teacher of the Kashmir. Hamza Makhdoom left luxurious life for Islam and Almighty Allah, because he knows the Allah Almighty says in the Quran, "I did not create jinn and mankind except to worship me" he also aware that without Deen-e-Islam there is no life. So he devoted his life for preaching of Islam. He did not followed Islam himself only but also taught that the people of Kashmir about Islam, that’s why thousands of followers of Hamza Makhdoom found in Kashmir. Secondary data is used in this paper